The use of the Butler Cycle and the Chaos Theory in the interpretation of the development of the Żegiestów-Zdrój health resort // Zastosowanie cyklu Butlera i teorii chaosu w interpretacji rozwoju uzdrowiska Żegiestów-Zdrój - Kruczek, Zygmunt (Geotourism/Geoturystyka, 2017)
In the article, the natural conditions and natural therapy facilities of Żegiestów-Zdrój – a small health resort in the Carpathian mountain range, have been described. In the course of the analysis of the development of this resort, R.W. Butler’s model of tourism area life cycle (TALC), was applied. The analysis has revealed that that the life cycle of Żegiestów-Zdrój has no predictable, linear form, and its course is extremely difficult to foresee, as is proved by the intermittent and unstable development line. The development of the health resort is better illustrated by the chaos theory which adopts the shape of a non-linear course of events. Supplementing the analysis of the life cycle with chaos theory has allowed the author to describe the course of development of Żegiestów-Zdrój in a much more precise way. In the summing up, the chances for a renaissance of the heath resort and an initiation of a new cycle of its development have been presented. The above theories may be applied the process of interpreting and forecasting changes in other health resorts. // W artykule opisano warunki naturalne i zasoby przyrodolecznicze Żegiestowa – niewielkiego uzdrowiska karpackiego. W analizie rozwoju tego kurortu zastosowano model cyklu życia obszaru turystycznego R.W. Butlera (ang. tourism area life cycle – TALC). Analiza wykazała, że cykl życia Żegiestowa-Zdroju nie ma przewidywalnej, liniowej postaci, a jego przebieg jest niezwykle trudny do odgadnięcia, czego wyrazem jest nieciągły i niestabilny przebieg zmian. Uzupełnienie analizy cyklu życia kurortu teorią chaosu pozwoliło na lepsze opisanie przebiegu rozwoju Żegiestowa-Zdroju. W podsumowaniu przedstawiono szanse na odrodzenia kurortu i rozpoczęcie nowego cyklu jego rozwoju. Opisane teorie mogą być wykorzystane w interpretacji i prognozowaniu zmian w innych uzdrowiskach.